IMPLEMENTASI APE DALAM MENSTIMULASI PERKEMBANGAN FISIK-MOTORIK ANAK - Nuni Yuniawati (LPPM Universitas Bina Bangsa, 2024)
This research was motivated by the results of the introduction of mass media which stimulated the physical motor development of children aged 4-5 years at RA Nurul Khoir Serang. Based on previous findings, there are still many children who are lazy in studying, children quickly complain of being tired when studying, and there is no stimulation for children in the media. The aim of this research is to analyze water supplies that improve the physical movement skills of children aged 4-5 years based on these results. This research uses a qualitative method using a descriptive approach. Observation, interviews and documentation were used as data collection techniques. Based on the research results, it was concluded that wells can help stimulate the physical motor development of children aged 4-5 years at RA Nurul Khoir Serang. This can be seen from the positive impacts that children receive, including: Children become more confident in trying new things, making coordinated jumping movements, throwing things in a controlled manner, knowing the order of the game, knowing the rules of the game, controlling hand movements. using uncoordinated fine muscles, eyes and hands when playing the medium well